2022
DOI: 10.3390/healthcare10020229
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians’ Social Support, Job Stress, and Intent to Leave Healthcare during COVID-19

Abstract: The onset of COVID-19 has escalated healthcare workers’ psychological distress. Multiple factors, including prolonged exposure to COVID-19 patients, irregular working hours, and workload, have substantially contributed to stress and burnout among healthcare workers. To explore the impact of COVID-19 on healthcare workers, our study compares the job stress, social support, and intention to leave the job among healthcare workers working in a pandemic (HP) and a non-pandemic hospital (HNP) in Turkey during the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“… 38 On the other hand, some studies found no relationship between the intent HCPs to leave the job and their socio‐demographic variables. 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“… 38 On the other hand, some studies found no relationship between the intent HCPs to leave the job and their socio‐demographic variables. 39 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…This was expected, as working with COVID-19 patients was a direct influencer of insomnia in the previous full-sample analysis and is concordant with other research studies. For example, the same distinction was found in healthcare workers from COVID-19 and non-COVID-19 hospitals [46]. Personal resilience is a well-characterized protector factor for insomnia and distress [47] and some organizations that have provided training to increasing resilience had positive effects on their employees.…”
Section: Discussionmentioning
confidence: 91%
“…The COVID-19 pandemic offers a particularly relevant context in which antecedents of eustress and distress can be reliably explored, also in cross-cultural studies, especially due to the global nature of the pandemic. A specific area of application of the short measure of eustress and distress is to better understand humans’ adaptation to the COVID-19 pandemic [ 21 , 22 , 40 ]. On the one hand, it is clear that the constant focus of the media and public discourse on the threats associated with the pandemic generate ruminative tendencies that predict self-handicapping tendencies and exhaustion [ 43 ], ultimately reducing wellbeing [ 40 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, Merino et al [ 18 ] used positive and negative affect experienced in relation to COVID-19 quarantine as indicators of eustress and distress, respectively. The COVID-19 pandemic is indeed a global stressor [ 19 , 20 , 21 , 22 ] that can trigger either eustress or distress in the population [ 20 , 23 ]. We have put forward a more comprehensive multidimensional approach of measuring eustress and distress in academic and organizational settings by taking into consideration emotional, physical, and behavioral indicators that discriminate between the two complex psychological states.…”
Section: Introductionmentioning
confidence: 99%